Effect of Repetitive Simulation Training on Emergency Medical Services Team Performance in Simulated Pediatric Medical Emergencies. Issue 3 (5th November 2020) - Kothari, Kathryn; Zuger, Chelsea; Desai, Neil; Leonard, Jan; Alletag, Michelle; Balakas, Ashley; Binney, Mike; Caffrey, Sean; Kotas, Jason; Mahar, Patrick; Roswell, Kelley; Adelgais, Kathleen M.
Abstract: Objective: Emergency medical services (EMS) professionals infrequently transport children leading to difficulty in recognition and management of pediatric critical illness. Simulation provides an opportunity to train EMS professionals on pediatric emergencies. The objective of this study was to examine the effect of serial simulation training over 6 months on EMS psychomotor and cognitive performance during team‐based care. Methods: This was a longitudinal prospective study of a simulation curriculum enrolling EMS professionals over a 6‐month period during which they performed three high‐fidelity simulations at 3‐month intervals. The simulation scenarios included a 15‐month‐old seizure (T0 ), 1‐month‐old with hypoglycemia (T1 ), and 4‐year‐old clonidine ingestion (T2 ). All scenarios were standardized and required recognition and management of respiratory failure and decompensated shock. Scenarios were videotaped and two investigators scored EMS team interventions during simulations using a standardized scoring tool. Inter‐rater reliability was assessed on 30% of videos using kappa analysis. Volumes of administered intravenous fluid (IVF) and medications were measured to assess for errors in administration. The primary outcome was the change in scenario score from T0 to T2 . Results: A total of 135 team‐based simulations were conducted over the study period (48, 40, and 47 at T0, T1, and T2, respectively). Inter‐rater reliability between reviewers was very good (κ = 0.7). Median simulation score improved from T0 to T2 (24 vs 31, p < 0.001, maximum score possible = 42). The proportion of completed tasks increased across multiple categories including improved recognition of respiratory decompensation (19% vs. 56%), management of the pediatric airway (44% vs. 88%), and timeliness of vascular access (10% vs. 38%). Correct IVF administration varied by scenario (25% vs. 52% vs. 30%, p = 0.02). Conclusion: Serial simulation improved EMS team‐based care in both recognition and management of pediatric emergencies. A standardized pediatric simulation curriculum can be used to train EMS professionals on pediatric emergencies and improve performance.